OPTIMALISASI PENERAPAN PERAWATAN HATCH COVER UNTUK MENGHINDARI KETERLAMBATAN PROSES MUAT BONGKAR PADA MV. CHANDRA KIRANA - Derma Watty Sihombing; Tri Kismantoro; Dio Triyuda Sisworo; Ronald Simanjuntak (Meteor STIP Marunda, 2023)
Hatch Cover is a part of the ship that is useful for protecting cargo from seawater and avoiding damage that can cause cargo damage. To make the load not damaged, of course, optimal maintenance is needed for the hatch cover and what needs to be applied in the maintenance of the hatch cover on the MV. Chandra Kirana so that damage can be avoided completely. The research method used is descriptive qualitative by describing the problem through observing what happens in the field, indirect interviews conducted with ship officers and crew, literature study, and documentation. By using this research method, the required data is obtained and then analyzed and presented with a descriptive narrative. From the results studied, it was found that there were problems with the application of hatch cover maintenance which was less than optimal and there were many obstacles encountered when carrying out hatch cover maintenance which resulted in delays in maintenance. Researchers suggest that companies can implement workshops for crew members who will board so they can know what to do in treating and repairing hatch cover damage and following hatch cover maintenance procedures in accordance with Doc. No. JSP E41 namely inspection and maintenance plan of bulk carrier hatch cover so that hatch cover maintenance can be carried out properly and reduce additional costs in the event of cargo damage